Belfast, Maine - Wiseman, Frederick; Davey, John (Frederick Wiseman - Intégrale Vol. 3: 1995-2016, 2016)
"Belfast, Maine" is a film about ordinary experience in a beautiful old New England port city. It is a portrait of daily life with particular emphasis on the work and the cultural life of the community. Among the activities shown in the film are the work of lobstermen, tug-boat operators, factory workers, shop owners, city counselors, doctors, judges, policemen, teachers, social workers, nurses and ministers. Cultural activities include choir rehearsal, dance class, music lessons and theatre production. [www.zipporah.com]